Bioassay of acaricide resistance on three common cattle tick species at Holotta, central Ethiopia - Jobre, Y.; Adamu, G.; Zerbini, E. (2001)
Bioassay of acaricide resistance on three common cattle ticks was carried out on four farms in Holotta area, Central Ethiopia, using a standardized FAO Acaricide Resistance Test Methods. Larval progeny of Boophilus decoloratus, Rhipicephalus e. evertsi and Amblyomma variegatum were subjected to larval packet test (LPT) employing four different acaricides (Dieldrine, Diazinon, Chlorfenvinphos and Coumaphos) each with five concentration levels. Strains of Boophilus decoloratus, Rhipicephalus e. evertsi, originated from an area where there is no tradition of acaricide application for tick control, were used as reference ticks. Extremely high susceptibility of reference tick strains was confirmed to all the tested acaricides. Statistical analysis of pooled mean mortality rates revealed that B. decoloratus strains were found resistant to Dieldrine and Diazinon in all studied farms; and to Chlorfenvinphos and Coumaphos only at the Sadamo farm. In addition, strains of R. e. evertsi from the research station farm revealed a slight degree of resistance to Coumaphos. A. variegatum strains from all farms showed high degree of susceptibility to all tested acaricides. The finding of organophosphate resistance is the first report of its kind in Ethiopia. Extensive uses of acaricides like BHC and Bacdip; irregular spraying, failure to maintain adequate lethal concentrations and other managerial constrains hampering the successful use of acaricides are anticipated causes of the emerging acaricide resistance in the study area. Pertinent recommendations were made to alleviate the existing problem in the study area as well as in other affected regions in the country.